Evidence-Based Pedagogy for Values Outcomes in Capstone Experiences - Julie Vale; Russell Kirkscey; James Weiss; Jenny Hill (Journal of the Scholarship of Teaching and Learning)
Undergraduate programs that focus on disciplinary knowledge and skills can reinforce pre-existing mindsets or ideologies that can lead to insufficient questioning of certain types of information (e.g., empirical data or model results) or insufficient valuing of certain types of information (e.g., Indigenous knowledge).  One way to address this challenge is to include values-based learning and assessment strategies that empower students to better understand and engage with their complex and changing worlds.  General Education (GenEd) Capstone Experiences (CE) often seek to instill such values, but scholarly analysis of the pedagogies and their effectiveness is limited, as is discussion on the inclusion of similar pedagogies in discipline-focused courses. This study addresses this research disparity by using a mixed methods approach to investigate student and faculty perceptions of the values integrated by a GenEd CE program and the pedagogies used to integrate those values.  Results demonstrate that the integration of reflection and discussion pedagogies has the potential to influence a variety of values-based outcomes, including thoughtfulness, openness, and responsibility.  Institutional leaders and CE instructors may integrate these pedagogies into their CEs, with mindful attention to the associated values that they seek to instill.